2021
DOI: 10.1038/s41598-021-93263-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of three double-microencapsulation methods for preservation of probiotic bacteria

Abstract: Lactic acid bacteria (LAB) are used as a probiotic alternative to antibiotics in livestock production. Microencapsulation technology is widely used for probiotic preservation. A variety of microencapsulation protocols have been proposed and compared based on chemicals and mechanical procedures. This study aimed to develop a double-encapsulated coating from alginate (1.5%) and chitosan (0.5%) by extrusion, emulsion, and spray drying methods using the LAB strains Lactobacillus plantarum strains 31F, 25F, 22F, Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…For example, they may secrete lactic acid, contributing to an acidic environment in the intestine, or produce bactericidal compounds, inhibiting the growth or adhesion of pathogenic bacteria. In previous in vitro investigations, cell-free supernatants of the live and microencapsulated forms of the three LAB strains used in this study have been shown to inhibit or kill ETEC strains 9 , 15 . In addition, LAB strains may compete for nutrients or binding sites on the epithelium and so prevent pathogen colonization 8 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, they may secrete lactic acid, contributing to an acidic environment in the intestine, or produce bactericidal compounds, inhibiting the growth or adhesion of pathogenic bacteria. In previous in vitro investigations, cell-free supernatants of the live and microencapsulated forms of the three LAB strains used in this study have been shown to inhibit or kill ETEC strains 9 , 15 . In addition, LAB strains may compete for nutrients or binding sites on the epithelium and so prevent pathogen colonization 8 .…”
Section: Discussionmentioning
confidence: 83%
“…Probiotic cell suspensions were subjected to double-coating microencapsulation with alginate and chitosan using the spray drying process, as previously reported 15 . In brief, for inner capsulation, a 1.5% (w/v) alginate solution (Sigma-Aldrich) was prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, regarding probiotic manufacturing, testing of spry-dried LAB subjected to elevated growth temperatures showed that after heat treatment at 60°C, the survival of heat-adapted L. cremoris and L. rhamnosus GG increased by 0.7-1.5 and 0.3 log, respectively [25]. In an evaluation of the preservation of LAB probiotics using 3 double-microencapsulation methods, microencapsulated LAB subjected to the 3 methods showed better tolerance of high temperatures (60 °C for 60 min, 70°C for 30 min, and 80 and 100°C for 30 s) compared to free cells [26]. Moreover, from several strains, L. casei showed the highest alfa-galactosidase stability in a study that tested potential probiotics and corresponding alfa-galactosidase for bean products [27].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, several techniques are reported to overcome these barriers, which enhance mucoadhesion properties and improve viability in the GI tract to increase colonization [19,20]. Microencapsulation has been recommended as a propitious solution to solve the issue regarding its viability and preservation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%